Sirtuins: The Future Insight - Suvarna, Bs (Kathmandu University Medical Journal, 2013)
Sirtuins are evolutionary conserved NAD+ dependent acetyl-lysine deacetylases and ADP ribosyltransferases dual-function enzymes involved in the regulation of metabolism and lifespan. Sirtuins represent a promising new class of III NAD dependent histone deacetylases that regulate a number of physiological processes, originally identified in yeast. Sirtuins regulate various normal and abnormal cellular and metabolic processes, including tumorgenesis, neurodegeneration and processes associated with type 2 diabetes and obesity. Several age-related diseases such as Alzheimer’s disease and longevity have also been linked to the functions of sirtuins. Because of these associations, the identification of small molecules sirtuin modulators has been of significant interest. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 77-82 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7350